RESPONSE OF MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) FAST FOOD TO THE OBLIGATION OF HALAL CERTIFICATION IN BIMA TOWN INDONESIA - Amrin Amrin; Al Mumtahanah Al Mumtahanah; Mas'udatul Fitriyah (Yurisprudentia: Jurnal Hukum Ekonomi, 2023)
This study aims to find out how the Response of Micro, Small, and Medium Enterprises of Fast Food to the Obligation of Halal Certification in the City of Bima, West Nusa Tenggara Province. This uses a type of qualitative research descriptive with a sociological approach. As for collection techniques namely observation, interviews, and documentation. While technique processing data analysis using reduction, data presentation, and conclusion. The results of this study indicate that first, the response of UMKM  in fast food regarding the understanding of halal certification has partially been understood even though details have not been conveyed. Second, UMKM response to PPH Act indicates strongly agrees with the existence of halal certification required by regulations to obtain halal guarantees from a food product served. Third, the response of UMKM  to the benefits of labeling halal certification provides a good value because in the future UMKM  want halal certification to be able to bring in material profit values as well as benevolent values (spiritual). Therefore, it is hoped that the latest Law will be a solution to various kinds of emerging problems and obstacles faced by UMKM.